Difference schemes for generalized solutions of some elliptic differential equations, I - Dung, Hoàng Đình (Journal of Computer Science and Cybernetics, 2016)
It is known that many applied problems are reduced to boundary value problems for differential equations with non-regular data. There are some works devoted to the construction of difference schemes and the estimation of approximate solutions for these problems [1-3]. In this work the difference schemes for generalized solutions of some elliptic differential equations are constructed. Here we first consider the partial differential equations with the right-hand side defined by a linear functional, for example, by the Dirac distribution δ.